Mission Impossible: Causes behind the Abandonment of Mission Stations in Nias between 1865 to 1890 - Dinkelaar, Bianca (Mission studies, 2025)
In places where, today, Christianity is successfully established, the historical narrative is often one of growth: tracing the path from the first converts to the seemingly inevitable triumph of Christianity. Within such a narrative, little attention is given to the failures and disappointments that occurred along the way. This article analyses a large collection of missionary letters from the recently digitized Nias archive of the Rheinische Missionsgesellschaft, to investigate the abandonment of three mission stations during the first decades of the mission. These stories of failure highlight how major factors, like colonial power, as well as idiosyncratic elements or even singular events, can steer the fate of a mission station in unexpected ways. The article aims to broaden knowledge of the early history of Niasan Christianity, and to show how points of divergence, misalignment and resistance can contribute to our understanding of the complex dynamics involved in missionary encounters.